Service Quality in Iranian Hospitals From Patients' Perspectives Based on the SERVQUAL Model: A Systematic Review and Meta‐Analysis - Tara Alizadeh; Marzieh Jahani Sayad Noveiry; Samad Karkhah; Ehsan Kazemnezhad Leyli; Kobra Salami Kohan; Pooyan Ghorbani Vajargah (Health Science Reports)
Abstract Background This study aimed to evaluate the service quality in Iranian hospitals from patients' perspectives based on the SERVQUAL model. Materials and Methods A thorough exploration of online electronic databases, including Scopus, PubMed, Web of Science, IranMedex, and the Scientific Information Database (SID), was undertaken using keywords extracted from Medical Subject Headings such as “Quality of Health Care,” “Hospital,” and “Patients” spanning from the earliest available records up to August 11, 2023. Results In the context of 25 cross‐sectional studies encompassing a collective participant pool of 8021 hospitalized patients in Iranian medical facilities, an assessment of patients' perspectives on the quality of hospital services revealed a mean perception score of 3.54 (SE = 0.08). Concurrently, the mean expectation score for the quality of services was determined to be 4.43 (SE = 0.06). Using the SERVQUAL model, the overall disparity between patients' perceptions and expectations was calculated as −0.89. Subsequent examination of specific dimensions within the SERVQUAL framework revealed gaps between patients' perceptions and expectations in the tangibility dimension (−0.84), reliability dimension (−0.94), responsiveness dimension (−0.91), assurance dimension (−0.89), and empathy dimension (−0.82). Conclusion Therefore, healthcare administrators consider the study's findings as a motivating force to initiate measures aimed at improving service quality in Iranian hospitals. Tackling the recognized shortcomings and areas requiring enhancement holds the promise of raising patient satisfaction levels and, consequently, improving overall healthcare outcomes.